1994
DOI: 10.1007/bf02249343
|View full text |Cite
|
Sign up to set email alerts
|

Platelet adenylate cyclase activity in israeli victims of iraqi Scud missile attacks with post-traumatic stress disorder

Abstract: Platelet adenylate cyclase activity was measured in 16 control subjects and 16 patients who developed post-traumatic stress disorder (PTSD) as a result of damage inflicted on their homes during the Iraqi Scud missile attacks on Israel which occurred during the 1991 Gulf War. There were no differences in basal, NaF-stimulated, PGE1-stimulated or forskolin-stimulated activity between controls and PTSD subjects. Epinephrine inhibition of forskolin-stimulated activity, an effect mediated by alpha 2 adrenergic rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…1 The relationship between the percentage of platelet 2 -adrenergic receptors in the high-conformational state (%R H ) and anxiety ratings in post-traumatic stress disorder patients low-affinity rauwolscine binding site is unclear since it has been shown that it is the agonist high-conformational (or affinity) state that mediates inhibition of AC (Thomson et al 1988). The upregulation in 2 AR density in the high-conformational state is consistent with observations of trends for increased epinephrine-mediated inhibition of forskolin-stimulated AC (Weizmann et al 1994). Low basal and forskolin-and aluminum fluoride-stimulated AC activity (Lerer et al 1987(Lerer et al , 1990 would have predicted downregulation of 2 AR density, particularly in the high-conformational state.…”
Section: Discussionsupporting
confidence: 82%
“…1 The relationship between the percentage of platelet 2 -adrenergic receptors in the high-conformational state (%R H ) and anxiety ratings in post-traumatic stress disorder patients low-affinity rauwolscine binding site is unclear since it has been shown that it is the agonist high-conformational (or affinity) state that mediates inhibition of AC (Thomson et al 1988). The upregulation in 2 AR density in the high-conformational state is consistent with observations of trends for increased epinephrine-mediated inhibition of forskolin-stimulated AC (Weizmann et al 1994). Low basal and forskolin-and aluminum fluoride-stimulated AC activity (Lerer et al 1987(Lerer et al , 1990 would have predicted downregulation of 2 AR density, particularly in the high-conformational state.…”
Section: Discussionsupporting
confidence: 82%